2020
DOI: 10.1111/jocn.15170
|View full text |Cite
|
Sign up to set email alerts
|

The significance of relationships and dynamics in families with a child with end‐stage kidney disease: A qualitative study

Abstract: Aim and objectives To explore experiences and the significance of relationships and dynamics among family members living with a child with severe kidney disease. Background Chronic kidney disease (CKD) in children is often incurable, leading to irreversible kidney damage. End‐stage kidney failure in a child impacts daily life and routines, requiring significant social adaptation for all family members. However, little is known about how individual family members experience relationships, interactions and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Some health professionals, more distant family members and friends provide significant support. The relationship with peers, that is, parents who have children in the same health condition, promotes a feeling of welcoming and belonging to society ( 38 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some health professionals, more distant family members and friends provide significant support. The relationship with peers, that is, parents who have children in the same health condition, promotes a feeling of welcoming and belonging to society ( 38 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some health professionals, more distant family members and friends provide significant support. The relationship with peers, that is, parents who have children in the same health condition, promotes a feeling of welcoming and belonging to society (38) . Spirituality, support strategy and coping in the route of young people with a chronic disease and their families (39) , was praised by the participants, from the diagnosis to all the experienced stages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies of siblings with other chronic conditions revealed that siblings also experience various feelings and reactions, such as sadness, anxiety, stress, or guilt over their good health [ 18 , 19 ]. Some of the problems commonly associated with CKD are summarized in Table 1 [ 20 - 34 ].…”
Section: Psychological and Social Problems In Children And Families W...mentioning
confidence: 99%
“…Nevertheless, children with CKD are exposed, and parents often experience difficulties in managing daily life in the family. Responsibilities-such as work, social life and caring for the other children-represent challenges that parents have to keep in balance, along with tending to the needs of their sick child (Agerskov et al, 2019(Agerskov et al, , 2020Cousino & Hazen, 2013;Cousino et al, 2017;Geense et al, 2017;Tong et al, 2010). Woodgate et al (2016) investigated how siblings experienced everyday life in a family with a child with complex care needs, as being a part of a group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CKD in children impacts the everyday life of all family members (Agerskov et al, 2019(Agerskov et al, , 2020Cousino et al, 2017). In particular, healthy children may be affected by the fact that the sick child needs the parents' special attention and engagement.…”
Section: Introductionmentioning
confidence: 99%